Different criteria of feed formulation for broilers aged 43 to 49 days - Araújo, LF; Junqueira, Otto Mack [UNESP]; Araújo, CSS [UNESP]; Faria, DE; Andreotti, MO (Fundação APINCO de Ciência e Tecnologia Avícolas, 2004)
An experiment was carried out to evaluate different formulated feeds for broilers from 43 to 49 days of age. Six hundred male Cobb broilers were distributed in a completely at random experimental design with 3 treatments (3 different criteria of feed formulation) and 4 repetitions per treatment, with 50 birds each. Diets were formulated with different criteria of digestible amino acid inclusion (methionine, methionine+cystine, lysine and threonine), according to the profiles recommended by Baker and Chung (1992), Degussa (1997) and Rostagno (2000) Live performance and carcass yield were evaluated in birds fed the different diets from 43 to 49 days of age). The profile established by Degussa (1997) resulted in best live performance. All profiles supplied the nutritional requirements of the birds for adequate carcass yield, but Degussa (1997) profile resulted in highest breast yield.
Keywords: Broilers; Carcass yield; Digestible amino acid; Performance